A chemical credit framework to predict the removal performance of organic chemicals of concern from water through an ozonation process. (1st April 2023) - Pang, Hongjiao; Zhang, Jianhua; Allinson, Mayumi; Gray, Stephen; Scales, Peter J.
Highlights: A credit framework to predict the chemical removal by ozone has been established. O3 /TOC ratio and O3 CT value to achieve predictive outcomes are demonstrated. Two chemical classifications to achieve chemical removal evaluation are indicated. UV254 and TOC as on-line surrogates for ozone barrier integrity are demonstrated. Abstract: Ozonation is an effective barrier for removing a wide spectrum of organic Chemicals of Concern (CoC) in a water treatment process. In this study, bench- and full-scale tests were conducted on a secondary treated effluent at the Eastern Treatment Plant (ETP) of Melbourne Water to probe the performance of ozonation in removing CoC in a wastewater discharge. From the secondary treated effluent as the feed to the ozone process, 58 organic chemicals were measured out of a possible 949 compounds by using the AIQS-DB analytical method. A chemical credit framework for the ozonation process has been established according to the bench-scale results. Chemical classifications based on the chemical structures (aromatics, aliphatic and halogenated aliphatic compounds) and reaction rate constants with O3 (KO3 ) and the ∙OH radical (K∙OH ) and a combined O3 /TOC ratio and O3 CT value as operating parameters were confirmed to be useful and important in determining whether a chemical would be removed by ozone. It is shown that an O3 /TOC ratio of >0.404 was shown to be necessary to overcome the instantaneous ozone demand (IOD) to guarantee enough ozone to oxidise CoC. For CoC with KO3 >10 5 M   −   1 s   −   1 and K∙OH >10 9 M   −   1 s   −   1, an O3 /TOC ratio of ≥0.461 or a measurable O3 CT of ≥0.063 mg min/L can achieve log reduction values (LRVs) of ≥1, these are chemicals with aromatic structures; For CoC with low KO3 and high KOH, a combined O3 /TOC ratio and O3 CT value inclusive of a chemical structure classification is indicated as necessary criteria to evaluate the removal. UV254 and TOC were demonstrated to be good online surrogates of ozone barrier performance in the absence of continuous O3 /TOC ratio and O3 CT value measurements. Full-scale operational results confirm the effective predictions of the chemical credit framework, which highlights the necessity and importance of monitoring both the O3 /TOC ratio and O3 CT values to predict the removal efficiency of a given chemical with a known response to O3 or a known chemical structure. Graphical abstract: Image, graphical abstract